Corpo e performance: um estudo sociocultural do tornar-se goleiro de futebol - Silva Segundo, Tarcísio Vieira de Lima (2024)
Considering the performative context in which the world of football is inserted, this study sought to understand the relationships between body perception, tiredness and emotions and how they manifest themselves in football goalkeepers. Using an interview script and supported by the phenomenological method, the narratives of twelve professional goalkeepers who played for football clubs in the north-east, south, south-east and central-west regions were listened to between July and August 2023 and then transcribed and analysed in accordance with the research objectives and the theoretical framework that included three authors: Maurice Merleau-Ponty, David Le Breton and Byung Chul-Han. The results gave us new insights into the body perception of goalkeepers, the manifestations of emotions and their respective relationships with fatigue, which distanced themselves from a merely technical view of these high-performance athletes. We believe that in the face of an excessive search for performance by these goalkeepers, their body perception becomes limited and lacks the depth to enable a broad understanding of this specific position. As for emotions, we understand that their manifestations are hindered by the behaviours and demands of the football universe, as evidenced in the narratives obtained. We understand that this study makes an important contribution to the socio-cultural field of football and to the training of professionals who work with the sport, whether they are coaches, specific goalkeeper trainers or other professionals directly linked to the sport.